Fatty acids in serum and diet – a canonical correlation analysis among toddlers. Issue 3 (8th November 2011) - Uusitalo, Liisa; Nevalainen, Jaakko; Salminen, Irma; Ovaskainen, Marja‐Leena; Kronberg‐Kippilä, Carina; Ahonen, Suvi; Niinistö, Sari; Alfthan, Georg; Simell, Olli; Ilonen, Jorma; Veijola, Riitta; Knip, Mikael; et al.
Abstract Fatty acid concentrations in blood are potential biomarkers of dietary fat intake, but methodological studies among children are scarce. The large number of fatty acids and their complex interrelationships pose a special challenge in research on fatty acids. Our target was to assess the interrelationships between the total fatty acid profiles in diet and serum of young children. The study subjects were healthy control children from the birth cohort of the Type 1 Diabetes Prediction and Prevention Study. A 3‐day food record and a frozen serum sample were available from 135 children at the age of 1 year, from 133 at 2 years, and from 92 at 3 years. The relationship between dietary and serum fatty acid profiles was analysed using canonical correlation analysis. The consumption of fatty milk correlated positively with serum fatty acids, pentadecanoic acid, palmitic acid and conjugated linoleic acid (CLA) at all ages. Correlations between dietary and serum eicosapentaenoic and/or docosahexaenoic acid were observed at 2 and 3 years of age. Serum linoleic acid was positively associated with the consumption of infant formula at the age of 1 year, and with the consumption of vegetable margarine at 2 and 3 years. The results indicate a high quality of the 3‐day food records kept by parents and other caretakers of the children, and suitability of non‐fasting, un‐fractioned serum samples for total fatty acid analyses. The correlation between intake of milk fat and serum proportion of CLA is a novel finding.